The influence of information asymmetry upon syndicated loan - Han, Cj (2014)
This study employed 14,372 syndicated loans in the US from 1997to 2006 to analyze the information asymmetry’ influence on lead arrangers and the participants. I use the moral hazard problem and information-selling hypothesis as theoretical framework and confirmed these frameworks with evidences. The indicator to measure the degree of the information asymmetry is the syndicated loan structure. And I find the evidence to prove how the information asymmetry can influence the loan structure and I also find the evidence to prove some factors can reduce the degree of information asymmetry, including the borrowers’ opaque, repetitive relationship between lender and borrowers and the arrangers’ reputation.